Exploration of the Environmental Characteristics of Kijang Waters (Sungai Enam Village) from the Perspective of Statistics and Development Potential: Eksplorasi Rona Lingkungan Perairan Kijang (Desa Sungai Enam) Dalam Persefektif Angka Dan Potensi Pengembangannya - Ma'mun*, Asep; Nugraha, Aditya Hikmat; Febrianto, Try; Kurniawati, Esty; Kurniawan, Rika; Suhana, Mario Putra (Universitas Lancang Kuning, 2025)
Sei Enam, which is located in Bintan Regency, is planned to become a modern village whose development is balanced between local culture and sustainable environmental practices (Rizki, 2023). Quantitative data obtained from environmental studies and direct measurements can be used as a measuring tool for assessing the development of tourism and aquaculture areas, with a focus on reporting plankton as a food source, oceanographic conditions and air quality (Azhar & Anuar, 2021). The research results show that the speed and pattern of tidal currents at the research location play an important role in each season in the distribution of water mass at the research location, while high waves are relatively small throughout the season, in line with the results of previous research (Rizal & Anwar, 2021). These air movement patterns play an important role in the distribution of food and nutrient sources in waters (Budiarto & Fathoni, 2019). The results of the land suitability analysis show that Sei Enam has an area of ​ ​303.73 Ha, which can be recommended as an area for developing cage-based floating restaurant culinary tourism. With the results of this area, the development of cage-based culinary areas can be carried out on a large scale, but this needs to consider other factors such as shipping lanes and ship docks (Halim & Rizal 2021). The results of the community response showed that 85% agreed with the development plan. The government's role in planning, implementation and commitment to activities is an important factor in sustainable development (Suharto & Astuti, 2020)